Pengaruh Penggunaan Youtube Sebagai Media Pembelajaran dan Motivasi Belajar Siswa Terhadap Engagement Belajar Siswa di SMA Negeri 8 Padang - Sherina Agvara Rizal; Nita Sofia; Yulhendri Yulhendri (Jurnal Pendidikan Ekonomi, 2022)
This study aims to determine the effect of the Youtube variable as a learning medium on student Engagement and to determine student learning motivation on student Engagement at SMAN 8 Padang. This type of research is descriptive with a causative approach, namely the existence of a relationship or influence with each other on the variables studied. The data will be taken through the process of distributing questionnaires that will occur during the 2021/2022 school year at SMAN 8 Padang. The data analysis method used is SEM (Structural Eguation Model) analysis with multivariate statistical analysis methods. The data will then be processed using the AMOS application which is then described by analyzing the obtained hypotheses and describing the results of the research. The results of this study indicate that there is an influence from the use of Youtube as a medium of student learning and student motivation on student learning Engagement at SMAN 8 Padang. So it is suggested to further researchers, can examine other learning media in the learning process and examine other variables that can increase student learning Engagement so that from the results of subsequent research new ways are found in increasing student learning Engagement so that it can improve the quality of the learning process.DOI: https://dx.doi.org/10.17977/UM014v15i22022p164